The low prevalence of colonic serrated adenocarcinoma with high KRAS mutational status at Cipto Mangunkusumo Hospital, Indonesia (Medical Journal of Indonesia, 2018)
Background: Serrated adenocarcinoma (SA), a subtype of colorectal carcinoma, and the KRAS mutation, a strong marker for the patient’s response to anti-epidermal growth factor receptor therapy, have a clinical importance because of its progressive nature and tendency for chemoresistance. The purposes of this study were to (1) determine the prevalence of SA, (2) evaluate the histomorphological characteristics of SA and classical adenocarcinoma based on its prognostic factors, (3) determine the prevalence of the KRAS mutation in SA cases, and (4) identify the main characteristics of SA cases and classical adenocarcinoma with a KRAS mutation.Methods: This study was conducted by reviewing hematoxylin-eosin-stained slides of colorectal carcinoma (CRC) cases from January 2013 to July 2015 at the Department of Anatomical Pathology Cipto Mangunkusumo General Hospital. The final diagnosis of SA was based on the Tuppurainen et al criteria and the KRAS mutation was evaluated using real-time polymerase chain reaction.Results: Among the 117 adenocarcinoma cases, there were 41 unequivocal SA, 11 equivocal SA, and 65 classical adenocarcinoma. The prevalence rates of unequivocal and equivocal SA among all CRC cases were 7.7% and 2.1%, respectively. There were 11 (28.2%) cases of wild-type KRAS and 28 (71.7%) cases of mutated KRAS among all unequivocal SA cases. Tumor budding (TB) was the predominant prognostic factor.Conclusion: The prevalence of SA among all CRC cases was 7.7%. The KRAS mutation was found in almost three-quarters of all SA cases.